From subsistence to profit: Transforming smallholder farms - Fan, Shenggen; Brzeska, Joanna; Keyzer, Michiel; Halsema, Alex (International Food Policy Research Institute, 2013)
Smallholder farmers in developing countries play a key role in meeting the future food demands of a growing and increasingly rich and urbanized population. However, small-holders are not a homogeneous group that should be supported at all costs. Whereas some smallholder farmers have the potential to undertake profitable commercial activities in the agricultural sector, others should be supported in exiting agriculture and seeking nonfarm employment opportunities. For smallholder farmers with profit potential, their ability to be successful is hampered by such challenges as climate change, price shocks, limited financing options, and inadequate access to healthy and nutritious food. By overcoming these challenges, smallholders can move from subsistence to commercially oriented agricultural systems, increase their profits, and operate at an efficient scale—thereby helping to do their part in feeding the world’s hungry.